Review of the Financial Sector Assessment Program : Further Adaptation to the Post-Crisis Era. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
The past five years have seen an expansion of the scope of FSAPs to assess countries' macroprudential policy (MaPP) frameworks. This note documents this increase and offers some suggestions on how the treatment of MaPP issues in FSAPs can be further strengthened and better integrated into the overall financial stability assessment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet